2004
DOI: 10.1152/ajpregu.00593.2002
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal hypometabolism as an overwintering strategy of red deer (Cervus elaphus)

Abstract: . Nocturnal hypometabolism as an overwintering strategy of red deer (Cervus elaphus). Am J Physiol Regul Integr Comp Physiol 286: R174-R181, 2004. First published September 11, 2003 10.1152/ajpregu.00593.2002Herbivores of temperate and arctic zones are confronted during winter with harsh climatic conditions and nutritional shortness. It is still not fully understood how large ungulates cope with this twofold challenge. We found that red deer, similar to many other northern ungulates, show large seasonal fluct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
143
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(170 citation statements)
references
References 64 publications
(62 reference statements)
22
143
1
Order By: Relevance
“…The occasional presence of LAGs in these large endothermic (nonhibernating and nonestivating) mammals led some (26) to conclude that such growth lines reflect phylogenetic legacy rather than a physiological response to environmental cycles or stresses. Nevertheless, evidence is accumulating that certain ungulates significantly reduce endogenous heat production to cope with energetically challenging situations (food shortage, harsh climatic conditions) (32). Thus, seasonal fluctuations in metabolic rate and in body temperature (heterothermy) have been described for ungulates with a winter nadir in northern species (32)(33)(34) and with a summer nadir in desert species (35,36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occasional presence of LAGs in these large endothermic (nonhibernating and nonestivating) mammals led some (26) to conclude that such growth lines reflect phylogenetic legacy rather than a physiological response to environmental cycles or stresses. Nevertheless, evidence is accumulating that certain ungulates significantly reduce endogenous heat production to cope with energetically challenging situations (food shortage, harsh climatic conditions) (32). Thus, seasonal fluctuations in metabolic rate and in body temperature (heterothermy) have been described for ungulates with a winter nadir in northern species (32)(33)(34) and with a summer nadir in desert species (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, evidence is accumulating that certain ungulates significantly reduce endogenous heat production to cope with energetically challenging situations (food shortage, harsh climatic conditions) (32). Thus, seasonal fluctuations in metabolic rate and in body temperature (heterothermy) have been described for ungulates with a winter nadir in northern species (32)(33)(34) and with a summer nadir in desert species (35,36). Taking into account these recent advances in ungulate physiology, the zonal bone of Myotragus quite likely reflects seasonal fluctuations in metabolic rate and/or body temperature over an extended juvenile period in response to fluctuating resource conditions on the island.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonality Like other animals, ruminants are subjected to seasonal rhythms of body mass gain or loss, food intake (Barry et al, 1991;Rhind et al, 2002), energy expenditure and metabolism (Mauget et al, 1997;Arnold et al, 2004) and reproduction (Asher et al, 1999;Santiago-Moreno et al, 2006). Two major mechanisms for this seasonality are recognised: the availability of resources (resource-induced seasonality) Figure 2 (a) Differences in relative dry matter intake (rDMI, per unit metabolic body weight; means, ranges and 25% to 75% percentile) between hindgut fermenters (n 5 49 species), nonruminant foregut fermenters (n 5 19) and ruminants (n 5 25) (data from Clauss et al, 2007b).…”
Section: Comparative Studies On Ruminantsmentioning
confidence: 99%
“…Low-quality food in the growing season or a reduced availability of high-quality food could have the same influence on survival of herbivores as extreme winters do. Arnold et al (2004) found that red deer, similar to many other northern ungulates, show large seasonal fluctuations of the metabolic rate, as indicated by the heart rate, with a 60% reduction at the winter nadir compared with the summer peak. A mechanism of energy conservation associated with peripheral cooling extensively lowers energy expenditure during winter.…”
Section: Discussionmentioning
confidence: 69%